(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
For addressing the issue of regional inequalities in access to STEM education, the STEM centres are located in Riga, the capital city of Latvia, as well as other cities, namely Cesis, Liepaja, Sigulda, and Ventspils, established in different regions of Latvia. A visit to a STEM centre in Latvia starts with the investigation of its online platform. The aim of this work is to build a framework for the analysis of online platforms of STEM centres in Latvia. The guiding research questions is: What are functions and sub-functions of online platform of the STEM centre? The descriptive study is employed in this work. The study is aimed at identification of functions and sub-functions of online platforms belonging to STEM centres. In the digital age, online platforms ensure links between STEM centres and their visitors. Online platforms of STEM centres provide important information about STEM centre’s aims, functions, facilities, and services. Online platforms also serve as a communication tool (use of emails and similar) between the STEM centre and its clients as well as stakeholders. The theoretical analysis allows shaping the framework for analysis of online platforms belonging to STEM centres. The framework is built of key functions (organisation contact information, educational programmes, and training to services) and sub-functions that online platforms are expected to present. The comparative analysis based on the descriptive study shows that only two online platforms provide the information about all the sub-functions highlighted in the developed framework. Two platforms mostly disclose the sub-functions, and one platform partly covers the necessary information. It should be noted that four STEM centres that fully or mostly reveal the sub-functions have been supported by Norway grants or belong to Riga Technical University. Our theoretical analysis is limited by the number of existing scientific literature in English. Theoretical analysis in other languages than English may advance further development of online platform for strengthening of STEM education. Another limiting factor is that online platforms were observed by the researchers who took part in this study. Interviews or surveys with the participation of online platforms’ users might lead to the creation of a framework with other key functions and subfunctions. Practical implications on a design of online platforms for STEM centres imply that online platforms should be user friendly. Another important aspect is to include all the organisations details such as name, a short description (year of establishment, staff number, etc), address and email, phone number, social media, and location on the map. In regard to educational materials, important is to give open access to the educational materials to all the users. This might increase their interest to visit STEM Centre in person. Another practical implication is to unite the five STEM centres in Latvia in one network and to establish close collaboration between them. This collaboration would support the whole approach to outdoor STEM education, the development of systemic, sequential, and gradual educational materials. This would increase learners’ understanding of STEM education as well as sustainable development of Latvia. The links between five STEM centres in Latvia should also be shown on their online platforms.